The relationship between quality of work life and organizational commitment among employees at Zun Utara Industry Sdn. Bhd / Mohd Firdaus Mohamad - Mohamad, Mohd Firdaus (2015)
The topic for this study is the relationship between quality of work life and organizational commitment at Zun Utara Industry Sdn. Bhd. The purpose of this study is to investigate and identify the relationship between quality of work life and organizational commitment at Zun Utara Industry Sdn. Bhd. Besides that, this study also wants to investigate the factors of quality of work life that influences the organization commitment in Zun Utara Industry Sdn. Bhd. Furthermore, this study also wants to investigate the the most contributing factors of quality of work life that influence commitment in Zun Utara Industry Sdn. Bhd. and also to determine whether is there any relationship between quality of work ie and organizational commitment in Zun Utara Industry Sdn. Bhd. The data finished through the questionnaire distributed to the employees at Zun Utara Industry Sdn. Bhd. which were 113 respondents in order to determine the relationship between quality of work life and organizational commitment. This study was found that there was a relationship between quality of work life and organizational commitment at Zun Utara Industry Sdn. Bhd.